Legalisasi Aborsi Bagi Korban Perkosaan dalam Perspektif Hak Asasi Manusia (HAM) - Guntara, Bima (Universitas Batanghari Jambi, 2025)
Legalizing abortion for rape victims is meant to improve the legal policy and enforcement of better and more accommodative to the protection of the victims of rape. Unborn babies also have the right to life. These differing perspectives on these two human rights have sparked much debate in society. This research is a normative legal analysis aimed at identifying legal concepts and doctrines related to the legalization of abortion for rape victims from a human rights perspective. The research approaches used in this study are the statute approach and the conceptual approach. The research approach used in this study is a statute approach and a conceptual approach. Research results (1) the government has issued regulations regarding the legalization of abortion for rape victims but does not have strong legal certainty. (2) The rights of women and the right of the fetus to life are equally protected by the laws of Indonesia. In the case of legalization of abortion for rape victims, the State applies the concept of limitation to the fulfilment of the right to life of the fetus, under the terms and conditions established by the Act governing the conditions and conditions permitted for abortions for the victims of rape.